The role of domestic ducks in the maintenance and spread of avian influenza viruses in Indonesia - Pabilonia, Kristy L., author; Bowen, Richard, advisor; Aboellail, Tawfik, committee member; Hyatt, Doreene, committee member; Knight, Anthony, committee member (Colorado State University. Libraries, 2012)
Wild waterfowl and aquatic birds serve as the natural reservoir host for influenza A viruses. As the reservoir, wild waterfowl play an important role in the persistence and transmission of influenza viruses among bird populations and to other mammalian species. In many Asian countries, domestic ducks are raised for meat and egg production. Some of these domestic ducks are ranged on rice paddies or post-harvest rice fields. The ducks provide service to the rice fields by fertilizing the field with feces and aerating the field by swimming and walking through the ground cover. Additionally, the ducks serve as a form of insect control through their natural grazing behaviors. The role that domestic ducks play in the ecology of influenza viruses is poorly understood. Highly pathogenic avian influenza H5N1 virus (HPAI H5N1) originated in Guangdong Province, China in 1996, which was followed by global dissemination of the virus that began in 2003. This virus is unprecedented in geographical spread, economic consequences and public health significance. At the present time, HPAI H5N1 virus is endemic six countries, including Indonesia. Indonesia has experienced the highest incidence of human infections with HPAI H5N1 virus and one of the highest case fatality rates. Control of the virus in Indonesia has proven extremely challenging, due to its diverse and complex poultry and domestic duck production systems. HPAI H5N1 virus is highly virulent in chickens and turkeys and causes severe systemic disease. Outbreaks of HPAI H5N1 in poultry populations are accompanied by high mortality. In contrast, HPAI H5N1 virus is typically nonpathogenic or mildly pathogenic in ducks and mortality in duck flocks during outbreaks of the virus is absent or limited. This allows ducks to serve as silent carriers of the virus, as they may shed large quantities of virus without displaying clinical signs of illness allowing infected ducks to evade detection by flock owners or government livestock officials. Domestic duck production is common in Southeast Asia. Indonesia has a large domestic duck population, estimated at more than 34 million ducks. Because HPAI H5N1 induces only mild disease in domestic ducks, outbreaks of the virus are difficult to detect and are rarely reported by domestic duck flock owners. Thus, domestic duck flocks have been left out of many government HPAI H5N1 surveillance and control programs. While a number of studies have demonstrated that the presence of domestic ducks in a country or at a specific location may be a risk factor for the presence of HPAI H5N1 virus, few studies have been conducted evaluating the role that domestic ducks play in the ecology of HPAI H5N1 virus. The objectives of the studies described in this dissertation were to elucidate the role of domestic ducks in the maintenance and spread of avian influenza viruses, particularly HPAI H5N1 virus, by evaluating domestic duck flock characteristics and behaviors, estimating the prevalence and incidence of avian influenza viruses in these flocks and characterizing HPAI H5N1 viruses detected in the field. To meet the objectives, two studies were conducted in West Java, Indonesia. The first study was a cross-sectional study aimed at characterizing domestic duck flocks and estimating the point prevalence and seroprevalence of avian influenza viruses, particularly HPAI H5N1 virus. This study was followed by a 7 month longitudinal study, aimed at estimating the incidence of avian influenza viruses, particularly HPAI H5N1 virus, in domestic duck flocks and evaluating flock illness and mortality during avian influenza virus outbreaks. A subset of samples from each of the studies was transported to the United States for virus characterization. The findings of the studies conducted demonstrate that domestic duck flocks are raised in complex production systems, are highly mobile, have significant contact with wild and domestic birds and mammals, are frequently ill and are provided with little formal veterinary care. The prevalence and incidence of avian influenza virus, including HPAI H5N1 virus, are high in domestic duck flocks in Indonesia. Clinical signs of illness and increased mortality did not correlate with the presence of avian influenza virus in the flock. Interestingly, there was also no correlation between increased flock mortality and the presence of HPAI H5N1 virus in the flock, demonstrating that domestic duck flocks can be asymptomatically infected with HPAI H5N1 virus while shedding high quantities of virus. Characterization of some of the viruses isolated from domestic duck flocks demonstrated that the flocks can be infected with more than one avian influenza virus at one time, as demonstrated by one flock that was positive for HPAI H5N1, as well as H3 and H7 avian influenza viruses. These situations are concerning, as domestic duck flocks may serve as mixing vessels for avian influenza viruses and co-infections in these flocks may result in the emergence of novel influenza viruses that may have capabilities for human-to-human transmission. It is likely that domestic ducks play an important role in the maintenance and spread of avian influenza viruses, including HPAI H5N1 virus. A number of domestic duck flock practices, including extensive flock movement, frequent introduction and sale of ducks, free-ranging of ducks in areas where they have contact with wild birds and animals and continual contact of duck flocks with other duck and poultry flocks, increasingly adds to the difficulty of control of HPAI H5N1 virus within this production system and makes eradication of the virus within a country extremely challenging.
Keywords: avian influenza; Indonesia; H5N1; duck; domestic duck; influenza